A Fluorine‐18 Radiolabeling Method Enabled by Rhenium(I) Complexation Circumvents the Requirement of Anhydrous Conditions. Issue 27 (11th April 2017) - Klenner, Mitchell A.; Pascali, Giancarlo; Zhang, Bo; Sia, Tiffany R.; Spare, Lawson K.; Krause‐Heuer, Anwen M.; Aldrich‐Wright, Janice R.; Greguric, Ivan; Guastella, Adam J.; Massi, Massimiliano; Fraser, Benjamin H.
Abstract: Azeotropic distillation is typically required to achieve fluorine‐18 radiolabeling during the production of positron emission tomography (PET) imaging agents. However, this time‐consuming process also limits fluorine‐18 incorporation, due to radioactive decay of the isotope and its adsorption to the drying vessel. In addressing these limitations, the fluorine‐18 radiolabeling of one model rhenium(I) complex is reported here, which is significantly improved under conditions that do not require azeotropic drying. This work could open a route towards the investigation of a simplified metal‐mediated late‐stage radiofluorination method, which would expand upon the accessibility of new PET and PET‐optical probes. Abstract : 18 and I like it : A novel fluorine‐18 radiolabeling method has been found to circumvent the need for preliminary azeotropic distillation. The method involves complexation to a rhenium(I) center, and is of particular importance in the expanded scope of positron emission tomography (PET) imaging agent design. Results were verified through the monitoring of multiple reaction conditions by employing microfluidic technologies in flow.